Percepção do método pilates como estratégia de intervenção terapêutica não farmacológica para idosos com câncer na atenção hospitalar: um olhar sobre a doença experiência - Cristina Carvalho de Melo (2022)
A person going through the process of aging must keep being active, through perfecting and seizing health opportunities, participation and security. Since the physiological, morphological and functional changes that occur during the natural aging process can negatively interfere in the functional capacity of the elderly, and the most important changes related to functional independence are changes in body fat, muscle strength, aerobic capacity and flexibility. Furthermore, damage to the psychological and social dimensions of individuals can further impair autonomy and independence. If, with advancing age, individuals tend to become more sedentary, the situation worsens with the diagnosis of a serious illness. Acknowledging the importance of physical exercise as a non-medicated and non-pharmacological therapeutic intervention strategy for elders in Health Care, new exercise proposals and methodologies are suggested for this intervention. In this context, the Pilates Method is brought forth which, due to its characteristics based on Contrology and global work in all exercises, also for looking at the person beyond quantitative data, focusing on a body-mind-spirit interaction, it has been indicated by several professionals, gaining adepts all over the world. However, the method is still little studied when compared to other exercise methods, mainly if we consider health care and psychosocial aspects. This study has a mainly qualitative approach and its goal is to observe and understand the subjects’ experience. The research universe was composed by 12 individuals with a cancer diagnosis who were inserted in Health Care. These individuals have volunteered to participate in the Pilates Extension Project offered by the responsible for this research in a Belo Horizonte hospital. As part of the understanding of how physical exercise, in this case the Mat Pilates, can contribute to life quality in the social and psychological context; and how these subjects interpret their experience, a semi structured interview and a participant observation were made. The interviews were made before the beginning of the Pilates Method intervention and three months after its conclusion. The technique used for the interview analysis was the dialectical hermeneutics, which makes the synthesis of the comprehensive and critical processes searching for the meaning comprehension that occurs in the communication between human beings, having language as its central core. The identified analysis categories were: “Pilates: an opportunity”; “Interpreting health”; “Interpreting the disease”; “Disease: news x acceptance”; “Pilates is movement”; “Pilates and socialization” and “Pilates: body-mind-spirit”. It is concluded that having a positive experience in hospital care and establishing new bonds and new concepts of belonging when experiencing the Pilates Method as a non-pharmacological therapeutic strategy was beneficial for the general quality of life of individuals. The act of getting involved and belonging to groups with which they have an affinity gave a new meaning to their days and generated a new strength in such difficult times, one day someone was inspired and the next became a reason for inspiration. And in all this scenario the Pilates Method has become a lifestyle transforming the body, mind and spirit of practitioners.